Teaching mathematics through story a creative approach for the early years - McGrath, Caroline (Routledge, Taylor & Francis Group, 2014)
"How do you make mathematics relevant and exciting to young children? How can mathematics and literacy be combined in a meaningful way? How can stories inspire the teaching and learning of mathematics? This book explores the exciting ways in which story can be used as a flexible resource to facilitate children's mathematical thinking. It looks at the potential relationship between story and mathematics and practically demonstrates how they can be combined to help children connect, understand and express mathematical ideas using story language; Written for all early years practitioners and students, the book offers a playful pedagogical approach to facilitating children's mathematical thinking which brings a creative satisfaction and confidence to teaching mathematics. Encouraging a creative approach to teaching mathematics that draws on picture books and oral mathematical stories, the book shows you how to: Move from reading to telling stories with mathematical themes Encourage children to pose and solve problems by playing with the plot of stories Enable children to translate abstract mathematical ideas to concrete representations with supporting story props and puppets Create original oral mathematical stories alongside children Capture children's mathematical thinking in an observational framework, supported with audio or video recordings which can be shared with parents and colleagues This book draws on practical work with children, educators, parents, professional storytellers, and trainee practitioners, who bring theoretical ideas to life and offer insight into their mathematical story experiences. It is a 'must have' for all those who want to make mathematics relevant, accessible and imaginative for young children"--Provided by publisher.